1998
DOI: 10.1098/rspb.1998.0578
|View full text |Cite
|
Sign up to set email alerts
|

Visual processing levels revealed by response latencies to changes in different visual attributes

Abstract: Visual latencies, and their variation with stimulus attributes, can provide information about the level in the visual system at which di¡erent attributes of the image are analysed, and decisions about them made. A change in the colour, structure or movement of a visual stimulus brings about a highly reproducible transient constriction of the pupil that probably depends on visual cortical mechanisms. We measured this transient response to changes in several attributes of visual stimuli, and also measured manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 17 publications
8
49
0
Order By: Relevance
“…That is, it may be that there is a restricted time window within which onsets can delay movement initiation. The similarity effect is presumably dependent upon color processing in the ventral extrastriate areas, which is likely to be slower than the processing of a luminance onset (Barbur, Wolf, & Lennie, 1998;Schmolesky et al, 1998). Therefore, the color-based similarity effect may take longer to develop (Ludwig & Gilchrist, 2003), and exert a more sustained influence on the response latencies.…”
Section: Contingent Capturementioning
confidence: 99%
“…That is, it may be that there is a restricted time window within which onsets can delay movement initiation. The similarity effect is presumably dependent upon color processing in the ventral extrastriate areas, which is likely to be slower than the processing of a luminance onset (Barbur, Wolf, & Lennie, 1998;Schmolesky et al, 1998). Therefore, the color-based similarity effect may take longer to develop (Ludwig & Gilchrist, 2003), and exert a more sustained influence on the response latencies.…”
Section: Contingent Capturementioning
confidence: 99%
“…The latency of the pupillary response to the test stimuli was calculated using the normalization technique developed by Barbur et al (1998). The time-courses for the earlier phase of the response (i.e.…”
Section: (A) Pupil and Accommodation Responses Evoked By The Isochrommentioning
confidence: 99%
“…jL7Mj+jL + Mj). Some researchers (Young & Alpern 1980;Barbur et al 1998) have demonstrated a di¡erence in the latency of pupillary responses between isoluminant and luminance stimuli, thereby suggesting that the balance between the di¡erent mechanisms is dependent on visual stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in more detail below, our low-saliency condition was defined as the 99% detection level for a colour or motion change. The high-saliency level was the point at which RTs became almost asymptotic (Barbur et al 1998).…”
Section: Methodsmentioning
confidence: 99%